The Influence of Electronic Word of Mouth (E-WOM) and Customer Trust on Purchasing Decisions in TikTok Shop(Case Study of STIE Makassar Maju Students) - Jumarlang, Indriani; Sultan, Sultan; Risman, Risman (Candela Edutech Indonesia, 2025)
The Objectives – This study aims to determine the influence of Electronic Word of Mouth (e-WOM) on Purchasing Decisions in TikTok Shop, 2) The influence of Customer Trust on Purchasing Decisions in TikTok Shop, 3) The influence of Electronic Word of Mouth (e-WOM) & Customer Trust simultaneously on Purchasing Decisions in TikTok Shop. The Methods/approaches – Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian Asosiatif kausal. Data dikumpulkan melalui penyebaran kuesioner offline yang disebarkan secara langsung dan kuesioner online melalui Google Form. Setiap variabel diukur dengan skala Likert kemudian diolah melalui SPSS 25 dimana analisis data yang tepat ialah analisis regresi linear berganda, uji t-parsial, dan uji F, dan uji koefisien detrminan. Teknik pengambilan sampel menggunakan metode purposive sampling dengan sampel akhir 81 responden mengggunakan rumus slovin. The Results – The results of the study indicate that electronic word of mouth and customer trust partially influence purchasing decisions. These two variables form a strong synergy in creating confidence and a sense of security when shopping at TikTok Shop. Therefore, it can be concluded that e-WOM and customer trust simultaneously act as important determinants in driving purchasing decisions of STIE Makassar Maju students. The Research Implications – This research contributes to the understanding of consumer behavior in social commerce, particularly on TikTok Shop. TikTok Shop needs to improve the quality of review content by encouraging buyers to provide more detailed reviews, demonstrating integrity by sending products as described, strengthening their ability to provide prompt service, and maintaining sincere communication to ensure consumers feel safe and comfortable shopping.